Reperfusion Times and Outcomes in Patients With ST-Elevation Myocardial Infarction Presenting Without Pre-Hospital Notification - Hamilton, G.W.; Yeoh, J.; Dinh, D.; Brennan, A.; Yudi, M.B.; Freeman, M.; Horrigan, M.; Martin, L.; Reid, Christopher; Yip, T.; Picardo, S.; Sharma, A.; et al. (2022)
Background: Primary percutaneous coronary intervention (PCI) for patients with ST-elevation myocardial infarction (STEMI) is recommended within 90 min of first medical contact. Those without pre-hospital notification (PN) are less likely to meet reperfusion targets and are an understudied subset of the STEMI population. Methods: An observational cohort study from a multicentre PCI registry of consecutive patients undergoing primary PCI for STEMI between 2012 and 2017. Exclusion criteria included out-of-hospital cardiac arrest, prior thrombolysis, symptom onset >12 h prior, and cardiogenic shock. Results: 2519 patients were included: 1392 (55.3%) without PN (no-PN group) and 1127 (44.7%) with PN (PN group). Those without PN had longer median DTBT (78 min vs 51 min, p < 0.001) and STBT (206 min vs 161 min, p < 0.001), with only 55% meeting DTBT targets out-of-hours in the no-PN group. No-PN patients had lower rates of AHA/ACC type B2/C lesions, GP IIb/IIIa use, aspiration thrombectomy and had smaller stent diameter (all p ≤ 0.003), suggesting smaller areas of ischemic myocardium. There were no significant differences in 30-day MACE (no-PN 5.6% vs PN 6.5%, p = 0.36) or long-term National Death Index linked mortality (no-PN 6.2% vs PN 7.9%, p = 0.09). Lack of PN did not independently predict long-term mortality. Conclusion: Despite comparably excellent outcomes overall, those without PN had longer ischemic times and were less likely to meet DTBT targets, especially after hours. Ischemic times may be a better evaluation of PN networks than hard clinical outcomes, and efficient systems of care tailored to the individual health service are essential to ensure timely reperfusion of patients with STEMI.